PERBEDAAN HARAPAN ANTARA AUDITOR DAN PENGGUNA DALAM TANGGUNGJAWAB AUDITOR, KEANDALAN DAN KEPUTUSAN YANG BERMANFAAT ATAS LAPORAN KEUANGAN YANG TELAH DIAUDIT - Yati Nurhajati (LPPM POLITEKNIK LP3I BANDUNG, 2015)
Through a questionnaire survey, this study investigated the existence and nature of an audit expectation gap in Bandung. A total of 46 auditors, 53 Banker and 31 investors responded to the questionnaire survey. Hypothesis testing used Kruskal Wallis Test to know audit expectation gap between auditor and users which were consisted of bankers and investors. The result of logic analysis showed the existence of significant expectation gap with respect to; (1) areas of auditor’s responsibility to prevention and detection fraud and illegal acts by clients, to prepare financial statements, to design and implementing internal control structure, to prepare accounting estimates, and reporting doubts as to an entity’s ability to continue as a going concern. (2) areas of reliability of audited financial statements based on assurance provided by an audit that auditor independence, reasonable assurance, and assurance that auditor detected of fraud and illegal client acts. The results indicate wide expectation gaps and misconceptions about audit in Bandung.